Diaspora politics : at home abroad - Sheffer, Gabriel (Cambridge University Press, 2003)
This book is about an important cultural-political phenomenon, ethno-national diasporas that try to feel at home in their host countries, and yet to maintain close contact with their homelands and promote their culture and interest. It discusses the complex questions of the loyalties of these groups to their homelands and host countries.